Pengembangan Desain Pembelajaran Basic Mathematic dengan Metode Estafet Kartu - Kresna Oktafianto; Eriska Fitri Kurniawati; Lilik Muzdalifah; Ahmad Zaenal Arifin; Nia Nurfitria; Afifah Afifah; Ridho Awanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
Basic education is very important for the next generation of the nation. A growing era requires educators to implement creative and innovative learning strategies. Basic education that is centered on elementary students is the center of attention, often mathematics lessons become a heavy scourge for elementary students. Therefore, learning mathematics in elementary students also requires learning strategies that are different from before. The purpose of the Rumah Matematika (RuMat) program for the community especially elementary students is to change the mindset of mathematics lessons that often scourge students into fun lessons by applying the Card Relay Method. The method is more in the form of a game so students can absorb knowledge while playing. With Rumah Matematika (RuMat) program, students will be more interested in learning basic mathematics in a more fun way.